Halal Label And Price Effect On Consumer Purchase Decision On Sedaap Mie Product - Kurniawan Yunus Ariyono (Jurnal Ilmu Manajemen Advantage, 2017)
The purpose of this study is to determine the effect of Halal Label and price partially and simultaneously to Consumer Purchase Decision on Sedaap Noodle Products. The research type used is descriptive with causal associative approach. This research was conducted with the number of respondents as many as 30 people. The sampling technique used is Simple Random Sampling technique. Hypothesis testing is done by multiple linear regression analysis for hypothesis through SPSS 16 for windows program. Based on research results obtained that partially label hala and price effect on consumer purchasing decisions on noodle products sedaap. While simultaneously halal label and price influence to consumer purchasing decision on noodle product sedaap. The amount of influence of halal label and price proved to have an effect on to consumer purchase decision on noodle product sedaap indicated by determination value (R2) equal to 0,61 while the rest equal to 39% influenced by other variable like product, place, promotion and others.